Orientale Basin as a Guide for Identifying Lunar Basin Datable Impact Melt and Assessing Impact Melt Differentiation - Kirby Runyon; James Head; Debra Buczkowski; Carolyn van der Bogert; Daniel Moriarty; Harry Hiesinger; Ben Greenhagen; Tyler Powell (The Planetary Science Journal)
Two fundamental questions face lunar scientists: (1) What is the absolute age of each lunar impact basin and thus the early impact flux curve? (2) To what degree did basin impact melt seas undergo differentiation? We compiled a 1:200,000-scale geological map of the lunar Orientale basin, focusing on identifying the most widespread and accessible occurrences of impact melt deposits from the basin-forming impact to help guide sample-return missions to Orientale and especially to other undated lunar basins using the identification and interpretation strategies for Orientale. We assess the size of craters excavating through basalt cap rock that may have exhumed datable basin impact melt, and we assess the possibility of impact melt sampling and melt differentiation for the large complex crater Maunder. We also provide guidance for distinguishing impact melt produced by larger complex craters from excavated basin melt and determining whether such craters may have also sampled through the entire melt deposit. Our analysis finds six such sites that are predicted to have the same age—that of the Orientale-forming event—and provides guidance for assessing possible melt differentiation. Future missions could collect samples from these sites for in situ age dating and petrologic assessment and/or for return to Earth and subsequent age dating and analysis. By sampling and dating impact melt of known provenance from the Moon’s dozens of large basins, future work can anchor the chronostratigraphy of the Moon’s formative years. Such information could be scaled to infer Earth’s large impactor flux around the time of life’s first emergence.